Physiological and perceptual responses to sprint interval exercise using arm versus leg cycling ergometry - Richard Metcalfe (Sports Medicine and Health Science, 2024)
Increases in power output and maximal oxygen consumption (V̇O2max) occur in response to sprint interval exercise (SIE), but common use of “all-out” intensities presents a barrier for many adults. Furthermore, lower-body SIE is not feasible for all adults. We compared physiological and perceptual responses to supramaximal, but “non-all-out” SIE between leg and arm cycling exercise. Twenty-four active adults (mean ± SD age: [25 ± 7] y; cycling V̇O2max: [39 ± 7] mL·kg−1·min−1) performed incremental exercise using leg (LCE) and arm cycle ergometry (ACE) to determine V̇O2max and maximal work capacity (Wmax). Subsequently, they performed four 20 s (s) bouts of SIE at 130 % Wmax on the LCE or ACE at cadence = 120–130 rev/min, with 2 min (min) recovery between intervals. Gas exchange data, heart rate (HR), blood lactate concentration (BLa), rating of perceived exertion (RPE), and affective valence were acquired. Data showed significantly lower (p < 0.001) absolute mean ([1.24 ± 0.31] L·min−1 vs. [1.59 ± 0.34] L·min−1; d = 1.08) and peak V̇O2 ([1.79 ± 0.48] L·min−1 vs. [2.10 ± 0.44] L·min−1; d = 0.70) with ACE versus LCE. However, ACE elicited significantly higher (p < 0.001) relative mean ([62 % ± 9 %] V̇O2max vs. [57 % ± 7 %] V̇O2max, d = 0.63) and peak V̇O2 ([88 % ± 10 %] V̇O2max vs. [75 % ± 10 %] V̇O2max, d = 1.33). Post-exercise BLa was significantly higher ([7.0 ± 1.7] mM vs. [5.7 ± 1.5] mM, p = 0.024, d = 0.83) for LCE versus ACE. There was no significant effect of modality on RPE or affective valence (p > 0.42), and lowest affective valence recorded (2.0 ± 1.8) was considered “good to fairly good”. Data show that non “all-out” ACE elicits lower absolute but higher relative HR and V̇O2 compared to LCE. Less aversive perceptual responses could make this non-all-out modality feasible for inactive adults.